EFECTOS DE LAS MAREAS Y DE LOS PERÍODOS INTRA ESTACIONALES EN EL COMPORTAMIENTO DE LOS CORMORANES PELÁGICOS (Phalacrocorax pelagicus Pallas, 1811) DURANTE EL BUCEO EN CATTLE POINT, SAN JUAN ISLAND, WASHINGTON, U.S.A - Manrique Bravo, Camelia (2016)
The influence of time of day, tidal depth, current and inside-season change on the diving behavior of pelagic cormorants, as well as the relationships between diving time and the preceding and the subsequent surface time were examined at Cattle Point, San Juan Island. Diving behavior was recorded using focal animal sampling. Dives and surfaces were timed to the nearest second. Correlations between dive time and the other variables were analyzed using regression analysis and t-test of significance. On a daily basis, dive times varied with time of day, tidal depth and current direction. Dive times were longer later in the day, showing a trend to be longer when height of the tide was higher and during ebb tides. However, dive times remained variable throughout the course of the season. No inside-season related variation on diving times was found, probably due to changes in prey availability. Mean dives and recovery times were 31.2 sec and 19.1 sec respectively showing that dive times were longer than surface times. Even so, positive relationships were found between dive time and the preceding surface time and between dive time and the subsequent surface time suggesting that cormorants utilize both anticipatory and reactive breathing according to the foraging environment.